HiTS: A High Throughput Memory Scheduling Scheme to Mitigate Denial-of-Service Attacks in Multi-core Systems - Shafaei, Mansour; Fei, Yunsi (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2014: Anais do XXVI International Symposium on Computer Architecture and High Performance Computing, 2014)
Sharing DRAM memory by multiple cores in a computer system potentially exposes the running threads on cores to denial-of-service (DoS) attacks. This issue is usually addressed by memory scheduling schemes that rotate the memory service among threads according to a certain ranking mechanism. These ranking-based schemes, however, often incur many memory banks' row-buffer conflicts which reduce the throughput of DRAM and the entire system. This paper proposes a new ranking-based memory scheduling scheme, called HiTS, to mitigate DoS attacks in multicore systems with the lowest performance degradation. HiTS achieves these by ranking threads according to each thread's memory usage/requirement. HiTS then enforces the ranking in a way that minimum performance overhead would occur and fairness is also balanced. The effectiveness of HiTS is evaluated by simulations with 18 different workloads running on 8- and 16-core machines. The simulation results show up to 15.8% improvements in terms of unfairness reduction and 24.1% in system throughput compared with the best existing scheduling scheme.